Postcolonial narratives and the governance of informal housing in London. Issue 2 (27th May 2021) - Schiller, Mariana; Raco, Mike
Abstract: Housing informality has traditionally been associated with cities in the Global South. And yet, there is growing evidence that informal practices are also present in Northern cities, especially those traditionally considered 'successful' or 'developed' such as London, in which housing pressures are most acute. This paper, drawing on detailed policy analysis and qualitative in-depth interviews, uses the example of London to examine the rise of informal housing, the ways in which it is both represented and conceptualised as a 'problem' of governance to be tackled, and its institutionalisation into programmes of enforcement. It focuses on the emergence of a phenomenon known as 'beds in sheds', or the construction of informal housing in between existing buildings. By discussing a planning issue that is generally associated with the Global South in a Global North context, the paper engages with writings on postcolonial theory. It adopts a nexus approach to examine how the issue is embedded within particular configurations of social, political, economic and cultural circumstances. The evidence indicates that the ways in which the problem is framed and understood are underpinned by colonialist views that see migrants and their socio-ethnic communities as agents of informality, whose removal or sanction will 'solve' the problem. The paper concludes with reflections on broader debates on informality in urban studies.